2017
DOI: 10.1371/journal.pgen.1006683
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping SETBP1 gain-of-function mutations in Schinzel-Giedion syndrome and hematologic malignancies

Abstract: Schinzel-Giedion syndrome (SGS) is a rare developmental disorder characterized by multiple malformations, severe neurological alterations and increased risk of malignancy. SGS is caused by de novo germline mutations clustering to a 12bp hotspot in exon 4 of SETBP1. Mutations in this hotspot disrupt a degron, a signal for the regulation of protein degradation, and lead to the accumulation of SETBP1 protein. Overlapping SETBP1 hotspot mutations have been observed recurrently as somatic events in leukemia. We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
92
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(103 citation statements)
references
References 67 publications
9
92
2
Order By: Relevance
“…Moreover, we found that p38β binding stabilizes the SET protein in the cytoplasm, demonstrating a new role for p38β. We had previously demonstrated that SETBP1 binds to and stabilizes SET, facilitating PP2A inhibition 25 , and this result has been confirmed in other reports 46,47 . Here we further characterize this mechanism by showing that p38β co-localizes with SET, SETBP1, and PP2A, regulating PP2A activity in AML cells.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, we found that p38β binding stabilizes the SET protein in the cytoplasm, demonstrating a new role for p38β. We had previously demonstrated that SETBP1 binds to and stabilizes SET, facilitating PP2A inhibition 25 , and this result has been confirmed in other reports 46,47 . Here we further characterize this mechanism by showing that p38β co-localizes with SET, SETBP1, and PP2A, regulating PP2A activity in AML cells.…”
Section: Discussionsupporting
confidence: 80%
“…A most recent study has proposed very surprising but interesting concepts by comparing somatic and germline SETBP1 mutations [71]. They described that consequence of SETBP1 mutations are different among substitutions in SETBP1 residues.…”
Section: Molecular Biologymentioning
confidence: 99%
“…On the other hand, substitutions in residue D868 led to the largest increase in protein levels. Cases with germline mutations affecting D868 have enhanced cell proliferation in vitro and higher incidence of cancer compared to patients with other germline SETBP1 mutations [71]. While these updated functional studies are helpful to understand biological mechanisms of leukemogenesis, therapeutic strategy to this distinct molecular target, SETBP1 mutation, is not established yet and requires further investigation.…”
Section: Molecular Biologymentioning
confidence: 99%
“…The gene was initially described as a translocation‐derived fusion gene in acute leukemia, where it has a proto‐oncogenic role (von Lindern et al., ). Strikingly, a dual role in cancer and ID/developmental disorders, respectively related to somatic and germline mutations, has been observed for numerous ID genes, such as SETBP1 , HRAS , EZH2 , SETBP1 , ARID1A , and ASXL1 and ASXL2 (Hoischen, Krumm, & Eichler, and references therein; Acuna‐Hidalgo et al., ; Ronan, Wu, & Crabtree, ).…”
Section: Discussionmentioning
confidence: 99%